Effect of vibration parameters in plasticizing process on properties of polypropylene by dynamic injection molding. (June 2015) - Wang, Quan; Qu, Jinping; Huang, Chaohua; Liu, Bin; Sun, Xiao
A novel self-designed dynamic injection molding machine by screw axial vibration introduced in plasticizing process was used in the preparation of polypropylene (PP) standard specimens. Under other process and same conditions, the vibration frequency and amplitude are changed in plasticizing process. The whole energy consumption in the molding process, the tensile stress, impact stress, density, and differential scanning calorimetric results of the specimens were measured. Furthermore, the effects of vibration parameters of plasticizing process on dispersion were studied with the mixture of PP and nano-calcium carbonate (CaCO3 ) materials using scanning electron microscopy (SEM). The experimental results showed that the maximum increment of tensile stress and impact stress of the specimens are 9.8and 13.8%, respectively, by screw axial vibration introduced in plasticizing process. The maximum increment of density is 0.3%. The melt point of specimens has a significant increase of 3°C and the energy consumption of the whole processing decreases 6.6% at maximum. The SEM micrographs show that the dispersion of nano-CaCO3 became more homogeneous compared with the steady specimens.